A revision of the South American genus Platycyamus Benth. (Leguminosae). Issue 1 (March 2016) - Moura, T.; Lewis, G.; Tozzi, A.
Summary A taxonomic revision ofPlatycyamus, a South American genus, is presented. The genus has traditionally comprised three taxa (two species, one with two varieties). All three are lectotypified in this study, but the infraspecific taxaP. regnellii var.glabrescens andP. regnellii var.regnellii are not recognised here as distinct. A key to distinguishP. regnellii fromP. ulei is presented together with species descriptions and the first published line drawings of the two.